Gap Affordance Judgments in Mixed Reality: Testing the Role of Display Weight and Field of View - Gagnon, Holly C.; Zhao, Yu; Richardson, Matthew; Pointon, Grant D.; Stefanucci, Jeanine K.; Creem-Regehr, Sarah H.; Bodenheimer, Bobby (Frontiers in Virtual Reality, 2021)
Measures of perceived affordances---judgments of action capabilities---are an objective way to assess whether users perceive mediated environments similarly to the real world. Previous studies suggest that judgments of stepping over a virtual gap using augmented reality (AR) are underestimated relative to judgments of real-world gaps, which are generally overestimated. Across three experiments, we investigated whether two factors associated with AR devices contributed to the observed underestimation: weight and field of view (FOV). In the first experiment, observers judged whether they could step over virtual gaps while wearing the HoloLens (virtual gaps) or not (real-world gaps). The second experiment tested whether weight contributes to underestimation of perceived affordances by having participants wear the HoloLens during judgments of both virtual and real gaps. We replicated the effect of underestimation of step capabilities in AR as compared to the real world in both Experiments 1 and 2. The third experiment tested whether FOV influenced judgments by simulating a narrow (similar to the HoloLens) FOV in Virtual Reality (VR). Judgments made with a reduced FOV were compared to judgments made with the wider FOV of the HTC Vive Pro. The results showed relative underestimation of judgments of stepping over gaps in narrow versus wide FOV VR. Taken together, the results suggest that there is little influence of weight of the HoloLens on perceived affordances for stepping, but that the reduced FOV of the HoloLens may contribute to the underestimation of stepping affordances observed in AR.